2012
DOI: 10.1002/ps.3304
|View full text |Cite
|
Sign up to set email alerts
|

Lethal doses of ozone for control of all stages of internal and external feeders in stored products

Abstract: This study confirms that higher doses and/or longer treatment times are necessary for control of internal stages of stored-product pests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 9 publications
2
46
0
1
Order By: Relevance
“…Lethal concentrations and exposure times for ozone have been reported to range between 5 ppm for 5 days (Mason et al 1997) to 135 ppm of ozone for 8 days (Hansen et al 2012) for insects living within stored products. The present study showed that a much lower concentration and time period (5 ppm for 120 min) can result in a substantial mortality of 12-day-old larvae of P. interpunctella when they were freely exposed to ozone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lethal concentrations and exposure times for ozone have been reported to range between 5 ppm for 5 days (Mason et al 1997) to 135 ppm of ozone for 8 days (Hansen et al 2012) for insects living within stored products. The present study showed that a much lower concentration and time period (5 ppm for 120 min) can result in a substantial mortality of 12-day-old larvae of P. interpunctella when they were freely exposed to ozone.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the feasibility of using ozone to manage stored product pests has received increased attention. Several studies have been carried out on the efficacy of gaseous ozone against stored product insect pests (Erdman 1980;Mason et al 1997;Kells et al 2001;Sousa et al 2008;Bonjour et al 2011;Hansen et al 2012). Ozone also has the potential for controlling insect strains that are resistant against phosphine (Zhangui et al 2003;Sousa et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full mortality of T. castaneum pupae and eggs and P. interpunctella eggs required a treatment of 180 min, and S. zeamais and S. oryzae, respectively, required 120 and 60 min at 1800 ppm ozone (MCDONOUGH et al, 2011b). Full mortality of the internal stages of eight species of Coleoptera and three species of Lepidoptera within kernels was observed when using 135 ppm ozone for 8 d (HANSEN et al, 2012). However, to implement the ozonation process in the milling industry, additional studies are needed to obtain information regarding the behavior of this gas in the flour.…”
Section: Introductionmentioning
confidence: 96%
“…For the adults' stages it required a CTP of 3,600 ppm-h for MW and 1,800 ppm-h for RW. Hansen et al (2012) achieved 100% mortality for adult saw-toothed grain beetle (SGB), Lesser Grain Borer (LGB), RFB, CFB, and IMM using a CTP of 5,040 ppm-h and 85% mortality for adult bread beetle (BB) in research trials using treatment chambers without grain. Also, their results indicated that a CTP of 25,920 ppm-h will be necessary to control all internal stages of granary weevil (GW), RW, and MW.…”
mentioning
confidence: 99%